Intertwined Languages and Broken Flows: Reading Ontological Polyphonies in Lower Murray Country (South Australia) - Camille Roulière (Angles, 2017)
In the context of severe environmental degradation, this article analyses governmental and Ngarrindjeri discourses surrounding the understanding and management of water in Lower Murray Country (South Australia). It shows that mutated colonial practices around water management in the Murray-Darling Basin have placed the Lower Murray region under unprecedented environmental threat. Future-oriented, paternalistic and linguistically intransigent poetics of elsewhere are used to justify the implementation of these monolingual practices, which gag alternative epistemologies. In response to this imperialistic water management (labelled as a second wave of dispossession), and strengthened by the growing recognition of Indigenous rights worldwide, Traditional Owners from the Basin have developed the concept of Cultural Flows to subtly subvert these silencing discourses and reclaim their right to a voice within governmental agencies involved in developing water management policies. This article argues that this reappropriated and re-rooted concept of Cultural Flows is merely the tip of a larger poetic shift in language, and can serve as a pivot around which to understand the mechanisms through which Aboriginal Nations, and in particular the Ngarrindjeri, weave their cultural practices, both figuratively and literally, within mainstream artistic and ecological discourses. Current manifestations of this shift, as expressed through visual arts (Riverland: Yvonne Koolmatrie, Art Gallery of South Australia), music (travelling performance project Ringbalin) and environmental politics (National Cultural Flows Research Project), are examined to demonstrate that this shift creates a new language which can be understood as a mode of highly localised Baroque speech (following Édouard Glissant’s definition of the term).